2000
DOI: 10.2139/ssrn.208291
|View full text |Cite
|
Sign up to set email alerts
|

Education, Work, and Crime: Theory and Evidence

Abstract: This paper develops and empirically examines a dynamic model of decisions to work, invest in human capital, and commit crime. By making all three activities endogenous, the model makes a number of new and interesting contributions to the study of crime. First, the model explains why older, more intelligent, and more educated workers tend to commit less of some property crimes than others. Age and education are more negatively correlated with crimes requiring little skill. Second, the model is useful for analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 33 publications
1
54
0
5
Order By: Relevance
“…Yet, little research has been undertaken to evaluate the importance of other types of external benefits of education, such as its potential effects on crime. (Lochner (1999) and Witte (1997) are notable exceptions.) Crime is a negative externality with enormous social costs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Yet, little research has been undertaken to evaluate the importance of other types of external benefits of education, such as its potential effects on crime. (Lochner (1999) and Witte (1997) are notable exceptions.) Crime is a negative externality with enormous social costs.…”
mentioning
confidence: 98%
“…(Of course, increased wages are an important consequence of schooling.) More recently, Lochner (1999) estimates a significant and important link between high school graduation and crime using data 1 activity is that unobserved characteristics affecting schooling decisions are likely to be correlated with unobservables influencing the decision to engage in crime. For example, individuals with high criminal returns or discount rates are likely to spend much of their time engaged in crime rather than work regardless of their educational background.…”
mentioning
confidence: 99%
“…A cursory reading of Dickens's Oliver Twist suggests the external benefits in lower crime from keeping young men in a monitored setting such as a school or a prison. Related to this, Lochner (1999) calculates that the social benefits from reduced crime associated with men graduating from high school are at least $7000 (1996 dollars), and perhaps considerably more.…”
Section: Discussion Of Acemoglu and Angrist's IV Resultsmentioning
confidence: 99%
“…The same idea has previously been discussed by Leigh (1998), who considers that a higher level of education is positive and direct correlated to the crime absence. This direct relationship has also been statistically tested by Lochner (1999), who concluded that the states with a higher school enrolment rate and with a strict legislation have the lowest criminality index.…”
Section: Human Capital and Social Cohesionmentioning
confidence: 97%